2022
DOI: 10.1167/iovs.63.6.19
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep Loss Causes Dysfunction in Murine Extraorbital Lacrimal Glands

Abstract: Purpose Sleep loss markedly affects the structure and function of the lacrimal gland and may cause ocular surface disease as a common public health problem. This study aims to investigate the circadian disturbance caused by sleep loss leading to dysfunction of extraorbital lacrimal glands (ELGs). Methods A mouse sleep deprivation (SD) model for sleep loss studies was built in C57BL/6J male mice. After four weeks, the ELGs were collected at three-hour intervals during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 121 publications
2
11
0
Order By: Relevance
“…Tear secretion was measured by intraperitoneal injection of pilocarpine hydrochloride (4.5 mg/kg) into mice (n = 6 at each time point) at ZT0, 6, 12, and 18, as previously described. 42 , 43 Ten minutes after drug administration, phenol red threads (no. 30059010; Tianjin Jingming New Technology Development Co., Tianjin, China) were placed in the inner canthi of the mice for 20 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Tear secretion was measured by intraperitoneal injection of pilocarpine hydrochloride (4.5 mg/kg) into mice (n = 6 at each time point) at ZT0, 6, 12, and 18, as previously described. 42 , 43 Ten minutes after drug administration, phenol red threads (no. 30059010; Tianjin Jingming New Technology Development Co., Tianjin, China) were placed in the inner canthi of the mice for 20 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, this asynchrony is present in the nutritionally challenged liver ( 54 ), as well as in several aging tissues ( 51 53 ). Recently, we found that the core clock of the lacrimal gland was not significantly altered, even in sleep deprivation-treated mice, without altering the light/dark cycle, although the output gene fraction was drastically altered ( 55 ). These studies further confirm the strong stability of the core clock without altering the day/night cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Time-series clustering approach is an effective way to assess temporal features associated with big data sets. 42 , 43 Four different types of rhythmic clustering oscillations are observed in the normal retina, each of them showing distinct pathway characteristics. However, significant variations in the circadian transcription landscape were observed after the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%